PENERAPAN BUSINNES MODEL CANVAS USAHA DAGANG ADFAR STORE GRESIK - Priya Adi Permana; Aries Kurniawan (CV. Denasya Smart Publisher, 2025)
This research aims to analyze the implementation of the Business Model Canvas (BMC) at Adfar Store Gresik, a trading business engaged in rice distribution. The BMC is used as a strategic tool to describe and evaluate nine key elements of the business: Key Partnerships, Key Activities, Key Resources, Value Propositions, Customer Relationships, Channels, Customer Segments, Revenue Streams, and Cost Structure. This research employs a qualitative phenomenological approach with data collection techniques through observation and in-depth interviews. The results show that Adfar Store Gresik effectively utilizes strategic partnerships, core activities, and key resources to improve operational efficiency and customer satisfaction. The main values offered include medium-quality rice, competitive pricing, and friendly service. In addition, distribution and communication strategies through social media and direct delivery services provide a competitive advantage in the market. The study concludes that the application of the BMC can help in designing a more structured business strategy, increasing competitiveness, and driving sustainable business growth.